2019
DOI: 10.9734/jpri/2019/v26i130125
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Phenolic Contents by HPLC, and Antioxidant, Antimicrobial, Antityrosinase, and Anticholinesterase Activities of Psephellus huber-morathii

Abstract: The goal of our study was to examine of antioxidant, antimicrobial, anticholinesterase activities, and phenolic composition of Psephellus huber-morathii. The antioxidant activities of extracts have been assessed by Ferric reducing antioxidant power (FRAP), cupric reducing antioxidant capacity (CUPRAC), and 2,2-diphenylpicrylhydrazyl (DPPH) radical scavenging. Phenolic constituents were measured using reverse phase-high performance liquid chromatography (RP-HPLC), and Korkmaz et al.; JPRI, 26(1): 1-10, 2019; Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The rich phytochemical profile of the hydroalcoholic extract better reflects the antioxidant ability, TPC, and TFC of the plant. The antioxidant activity and TPC findings in this study support previous findings about PH (Sarker et al, 2005;Korkmaz et al, 2019).…”
Section: Antioxidant Activities Tpc and Tfcsupporting
confidence: 92%
See 3 more Smart Citations
“…The rich phytochemical profile of the hydroalcoholic extract better reflects the antioxidant ability, TPC, and TFC of the plant. The antioxidant activity and TPC findings in this study support previous findings about PH (Sarker et al, 2005;Korkmaz et al, 2019).…”
Section: Antioxidant Activities Tpc and Tfcsupporting
confidence: 92%
“…Besides the major compounds, PH contains high amounts of quercetin-3-glucuronide (9.04 mg analyte g extract -1 ), isoquercitrin (6.62 mg analyte g extract -1 ), quercitrin (6.82 mg analyte g extract -1 ) and apigenin (2.43 mg analyte g extract -1 ). Two HPLC studies were reported for the phenolic compounds of PH (Korkmaz et al, 2019;Shoeb et al, 2007). Korkmaz et al identified 7 compounds in the methanol extract of the plant and quantified two of them.…”
Section: Lc-ms/ms Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Signals were identified using DAD detection at a column temperature of 25ºC. HPLC analyses were performed modified methods in our previous study [17,18].…”
Section: Tyrosinase Inhibitionmentioning
confidence: 99%